Effective strategy making: Co-designing scenarios as a tool for effective strategic planning - Vogelij, Jan (A+BE | Architecture and the Built Environment, 2015)
Subject of this study For establishing main lines of their future development, governments on several levels of government prepare spatial development visions, for assessing individual plans and initiatives against the background of a desired direction of development. Such strategic visions help to avoid the necessity to start considering again and again the question which direction long-term development should take. The European Commission promotes making such development strategies, hoping this leads to innovation in the regions and increased competitiveness of Europe. More particularly, the Commission expects a substantial contribution to prosperity of the rich diversity of local characteristics as assets for the development and innovation of the European territory. This study aims to explore the factors for success of strategic spatial planning. Strategy making happens in the different circumstances in European countries, legally regulated or informally, using terms like: Structure plans, structural visions, master plans, development visions and spatial development strategies. Here the term (spatial) development vision is used. The central question is: Which aspects of planning processes and place-related conditions support the effectiveness of strategy making? The processes of strategy making and the place related circumstances are intensively interrelated. The diversity of circumstances in the European countries is expressed in the different national and regional planning cultures. That includes the set of procedures, competencies, education of planners and other experts and their resulting attitudes towards strategy making. In a development strategy all interests of society come together. Therefore the constructive working together of representatives of different sectors and interest is key to the success. Because of this crucial issue, we distinguished between co-operation, as just contributing to someone else’s activity, co-producing, as making together a product and collaboration towards a strategy, defined as a common exploration of possibilities. The interactions of the participants in the strategy making process, potentially creating trust and enhancing social cohesion, may be more important than the resulting concept for a development strategy. Therefore our attention focused on the way strategies are made in the black box of specific processes. The interactions aiming at co-ownership and collaboration are central in this novel ’interactions approach’. The resulting strategy does not necessarily contain (infra) structural projects; a spatial strategy concerns a selected localised policy and argumentative framework for future development. Societal relevance Being a planning consultant with over forty years of experience in practice, the author highly values practical applicability in society. Understanding of practice-related factors for effectiveness of strategy making is important because effective public management saves costs for society; a framework expressing the aimed-for direction of development provides clarity for private initiatives; an agreed strategy helps to coordinate sector policies; several EU and national subsidies for projects require a locally agreed structural frame. Because a development vision concerns the direction of an envisaged development, its effectiveness is defined in terms of performance of the argumentative framework based on the story lines developed in the discussions during the strategy making process. Our search aims at identifying recommendations for enhanced chances for performing strategies in praxis. Approach A theoretical frame was composed based on literature in the fields of planning theory, policy analysis and design. Research questions were formulated concerning the importance of the process related variables: open process management, coownership, co-design, the application of scenarios and visualizations. Concerning the importance of the place related aspects, research questions consider: planning culture, multi-level embedding, involvement of politicians and the experiences of actors in previous processes. The explorations for composing the theoretic frame aimed to do justice as much as possible to the complexity of network society in which a strategy has to be agreed. First (im-) possibilities for governing public administrations in network societies are explored. That exploration concluded that since the authority of data, experts and politicians are not self-evident anymore; there is a greater need than before that actors become convinced by arguments. Not interests as they see it (differently) but story lines support converging to an agreed selection of located objectives. Strategy making should therefore be organized as a societal process aimed at sharing ownership of ideas among participants. The second exploration for composing the theoretic frame considered conceiving a development strategy as a decision-making process. The interdependencies of social, economic, ecologic and man-made physical systems in a territory require integrated decision-making involving the relevant interests. Acknowledging that the representatives of different sectors and non-governmental and private organizations foster different views on reality, implies that the specific procedures of spatial planning will generally not be accepted by all, as the procedure for the strategy making process. That entails decision-making occurring in a non-envisaged number of rounds of decision-making in different groupings. The ultimate success of a long-term development policy consists of flexible but continued application of the argumentative frame of the strategic vision. Fairly assessing long-term strategies requires evaluation, often decades after deciding on the strategy. Society seldom allows that time for assessing the success of a strategy because different urgent issues developed since it’s making and the vision became a “historic” view in the eyes of many. Therefore a different approach for establishing expected success was needed. The specific, pivotal round of deciding about the concept of a strategic vision is called here effective, if the agreed strategy as resulting from that round of decision-making is expected to eventually perform. But effectiveness of decision-making is not sufficient; an effective strategy also implies a new promising perspective for the development of a territory. Effective decision-making consisting of effective continuation of an existing trend or more efficiently deciding on a concept does not need a strategic development vision. Those activities are not considered here for effective strategy making. Therefore, the third exploration for composing our strategic frame focused on creativity as a requirement for discovering a novel direction of development. Discovering new possibilities for developments and re-interpreting existing qualities for new applications require an open creative approach. Design is needed for expanding the possibilities of what society sees as a probable future and above all for avoiding that the search for innovation would be restricted to what important actors consider possible. Central is the search for agreement about a desired future and how to make it possible. A process of co-designing a new vision of the desired future, whereby participating actors become co-authors of something not-existing before is assumed to bring about stronger and longer lasting commitment, which is essential for the long-term success. The assumed larger commitment would result from the combination of a maximal open process of decision-making like in designing, in which ideas of every participant are welcomed as valuable contributions and which takes the freedom of not starting by accepting limitations and conditions as coming from several sides. Such creative process is expected entailing forms of co-authorship. Important is that the relevant higher government level approaches the process positively and supportive, although without unconditional commitment to any outcome of the process. The empiric part contains case studies of five strategy making processes in different European countries. The selection of cases was based on a pre-selection proposed by planners, representing their countries in the European Council of Spatial Planners (ECTP-CEU) They responded to the request for good examples of cases of successful strategy making in their countries. The final selection of five was chosen applying practical considerations about expectations of local help in assembling information. The selected cases were: Piano Strutturale Comunale of Bologna (IT), Scenariostudie Drechtsteden 2030 (NL), the Glasgow and the Clyde Valley Strategic Development Plan (UK), Vision Gherdëina (IT) and Meetjesland 2020 (BE). Next to plan documents and existing evaluations, forty-one interviews formed important sources of information for connecting casuistic and theory. Applying our definition of effectiveness, first the effectiveness of our cases was established. Not all of those five appeared to be effective according to our criteria as formulated in the theoretical frame. Next the cases were analysed, using pre-formulated hypotheses for process and place-related conditions influencing the performance of spatial development strategies. The accounts of cases in different planning cultures related to the process and place-aspects of the theoretic frame provided insight in the different process aspects and the circumstances in which those processes were conducted. That, in combination with the earlier established (non-) effectiveness enabled characterizing the processes within their various administrative and societal environments. Subsequently the process aspects and the place-related aspects of the five cases were compared and analysed applying the research questions, the hypotheses and the chains of evidence. Such comparison allowed for conclusions about factors for effectiveness. Conclusions The study did not provide evidence that strictly regulated, rigid planning cultures were prohibitive for strategy making. In all five processes a form of co-production existed, which in most cases resulted in some form of co-ownership of the results. Co-ownership evaporated soon in the cases that were not qualified as effective. Remaining co-ownership appeared to be most important for the eventual success of the spatial development vision. That has been established in Drechtsteden, Glasgow and Grödental (Vision Gherdëina). The strategy making in Bologna and Meetjesland was not successful. In Bologna lack of success resulted from extensive procedural requirements, political instability and the complexity of the administrative embedding, despite a strong concept for future development. In Meetjesland the failure was related to the lack of a sound administrative embedding together with insufficient specificity of the vision: a set of nine objectives without concrete elaborations and selective site locations did not build lasting support. The study confirmed that effective decision-making processes for long-term developments are open, interactive collaborations towards new concepts applying visualizations (maps) and the related storylines of representatives of the interests that are considered relevant locally. Although the selection of cases consisted of processes, which were found successful by planners of the country in which the cases are located, two of the cases were not effective according to our criteria. Not only satisfaction about the initial result and a form of co-ownership was important, the continuation of the processes in subsequent rounds of decision-making was even more important. The openness of decisionmaking is of special importance for converging to an agreement. Introduction of a design attitude in strategy making, applying maximal openness results in creating coauthorship, which entails stronger, lasting commitment to the agreed vision. Here the specific attitude is not meant of some, who concentrate on conditions and on mapping the limitations set by what important actors see as possible or feasible as a starting point. That approach tends to design in the limited space left over by other sector’s claims. Designing as meant in the current study regards the open “what if, then that” iterations during which designers focus on exploring new possibilities, not respecting conditions and limitations in advance. Preparing a spatial development strategy as a societal decision-making process by applying an open design attitude implies generating ideas, assessing, correcting, improving and refining solutions. The study confirmed the importance of visualizations as tools for enhancing the effectiveness of communication during the collaborative process. In order to open up minds for different ways of viewing during the process and to do justice and pay respect to ideas of the participants, decision-making is preferably organized as scenario planning, considering simultaneously several options and in which every tabled idea is considered and assessed according to its potentials, (im)possibilities and consequences. Discovering new possibilities together and co-designing a desired future entails co-authorship, which goes beyond and enhances co-ownership. This also applies for the administrative embedding: in two of the three successful cases the higher level authority acted as co-authoring partner of the development vision. Important for such vertical commitment is that the number of administrative layers with which the strategy making process must relate, should be small: preferably only one higher authority. In such cases, the strategy making process will not become an arena in which several higher authorities conduct their institutional policies for fighting their struggles for hierarchy. The only (approving) authority can support the process according to its commitment and act as a partner. Acknowledging that the responsibilities of a higher authority do not allow full commitment in advance to a yet unknown output, applying a form of loose coupling is helpful. This implies that the higher authority supports the process and commits to positively considering consequences of the output, provided that specific process conditions are fulfilled. This especially applies if envisaged large infra structural projects require substantial investments of higher authorities. The study confirms the importance of involving spatial designers and a design attitude in the collaborative decision-making process towards long-term development strategies. The necessary openness of such processes requires conducting designing not as a person-focused internal activity but to design as a process of group creativity in the collaboration of relevant participants. The ‘interactions approach’ provided useful conclusions and contributes as a novel to existing planning theory.